Four new species of Alloxysta (Hym.: Cynipoidea: Figitidae: Charipinae) from Petr Starý’s collection - Ferrer-Suay, Mar; Pujade-Villar, Juli; Selfa, Jesús (European Journal of Taxonomy, 2023)
After the revision of Petr Starý’s Charipinae collection, four new species of Alloxysta Förster, 1869 have been found. This collection represents a good overview of the Charipinae fauna worldwide, although the best represented area is Central Europe. Here, we describe four new species of Alloxysta: A. llumae Ferrer-Suay sp. nov., A. onae Ferrer-Suay sp. nov., A. poli Ferrer-Suay sp. nov. and A. staryi Ferrer-Suay & Pujade-Villar sp. nov. Three of these new species are based on reared specimens. Diagnosis, distribution, and description of the new species are given and illustrated.